EPIC® and High Reliability in Healthcare: An Evidence Based Commentary - J. Johnson, Ralph (Journal of Medical Informatics and Decision Making, 2024)
This evidence-based brief commentary discusses the potential of EPIC ® medicalrecords software to help or hinder in advancing High Reliability in healthcare—namely, the intent to attain repeatable, increasingly high levels of quality and safety over time. Four of EPIC’s key aspects relevant to High Reliability are examined: Standardized (High Quality) Information / Data Collection, Technological Somnambulism, Enhanced Patient Safety, and Reminders / “Hardstops.” A conclusion is drawn that EPIC, if used correctly, has vast potential to advance High Reliability high-quality and safety, specifically in medical treatment and regarding healthcare organization practice in general. However, it has hidden costs that are more than money; if unfettered, those costs can hinder its usefulness and even render it counterproductive. EPIC only works well in terms of Maximum High Reliability in healthcare as long as users and leaders remain mindful, prudent, and balanced in its use.
Keywords: High Reliability; Electronic Health Records; EHR systems; EPIC software; Healthcare Information Technology; Meaningful Use; Mindfulness.